Serological Correlate of Protection Established by Neutralizing Antibodies Differs Among Dialysis Patients with SARS-CoV-2 Variants of Concern - Guy Rostoker; Stéphanie Rouanet; Myriam Merzoug; Hiba Chakaroun; Mireille Griuncelli; Christelle Loridon; Ghada Boulahia; Luc Gagnon (Vaccines)
Background: The 2019 coronavirus disease (COVID-19) pandemic had a severe impact on frail, end-stage kidney disease (ESKD) patients, either on dialysis or transplanted, with a high mortality rate in the early waves. Vaccination against SARS-CoV-2 with mRNA vaccines has led to reduced hospitalization and mortality rates in the general population and ESKD patients. Neutralizing antibodies (NAbs) are a valuable correlate of protection after vaccination, and IgG anti-spike antibodies are considered a surrogate marker of protection. Methods: This study investigated the correlates of protection brought by NAb and anti-spike IgG antibodies against SARS-CoV-2 wild-type Wuhan strain and variants of concern in a cohort of 128 French patients on dialysis after vaccination with the BNT162b2 mRNA vaccine. The correlate was assessed using Receiver Operating Characteristic curves. Results: The level of protection for IgG anti-spike antibodies was set at 917 BAU/mL for the original Wuhan strain and 980 BAU/mL and 1450 BAU/mL, respectively, for the Delta and Omicron BA.1 variants. Conclusions: The level of protection can be regularly monitored by measuring IgG anti-spike antibody concentrations to allow tailored boosters of SARS-CoV-2 vaccination in this frail and immunocompromised ESKD population.